Kader Siaga ASI: Penyegaran Pemahaman Laktasi bagi Aisyiyah dan Nasyiatul Aisyiyah - Suparni Suparni; Isyti'aroh Isyti'aroh; Nurul Aktifah; Nina Zuhana; Ratnawati Ratnawati; Herni Rejeki; Siti Rofiqoh; Windha Widyastuti (Jurnal LINK, 2026)
The success of breastfeeding is strongly influenced by the knowledge and skills of those who support mothers, including community health cadres. Aisyiyah and Nasyiatul Aisyiyah cadres play an important role in providing breastfeeding education at the community level; therefore, they require adequate knowledge and practical skills related to lactation management. This community service program aimed to enhance the knowledge and skills of Aisyiyah and Nasyiatul Aisyiyah cadres in delivering education on breastfeeding and the benefits of breast milk. The training consisted of lectures, group discussions, demonstrations, and hands-on practice facilitated by experts in midwifery and maternal nursing. Knowledge improvement was assessed using pre-test and post-test evaluations, while skill acquisition was observed during practice sessions. A total of 32 cadres participated in the activity. There was an increase in knowledge after the training, with the mean pre-test score rising from 80.94 to 84.53 in the post-test, showing an increase of 3.59 points, Cadres also demonstrated improved skills in breastfeeding positioning, attachment techniques, and identification of lactation problems such as flat nipples and breast engorgement. The refresher training effectively improved the cadres’ competence in providing breastfeeding education. It is recommended that similar programs be conducted regularly to strengthen the role of cadres in supporting breastfeeding mothers in the community.